2009
DOI: 10.3402/ijch.v68i1.18300
|View full text |Cite
|
Sign up to set email alerts
|

Trends in physical activity in Greenlandic schoolchildren, 1994–2006

Abstract: Objectives. To describe trends in self-reported physical activity among Greenlandic schoolchildren from 1994 to 2006, and to analyse associations between physical activity and quality of life, health, academic achievement, school satisfaction and substance use. Study design. Trend analysis of the Greenlandic data reported in the Health Behaviour in SchoolAged Children (HBSC) survey on , , and 5 years olds in 994, 998, 00 and 006. Methods. Analyses of associations data on all participating children in Greenland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(7 reference statements)
0
3
1
Order By: Relevance
“…This finding seems to concur with some studies among college students [8] but not with other studies on adolescent school children [3,4,6,10]. While this study found that tobacco and illicit drug use were not associated with physical activity, other studies found an inverse association between physical activity and tobacco and illicit drug use [2,3,6,7,10,11]. Furthermore, this study found that higher socioeconomic status was associated with participation in more frequent physical activity.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This finding seems to concur with some studies among college students [8] but not with other studies on adolescent school children [3,4,6,10]. While this study found that tobacco and illicit drug use were not associated with physical activity, other studies found an inverse association between physical activity and tobacco and illicit drug use [2,3,6,7,10,11]. Furthermore, this study found that higher socioeconomic status was associated with participation in more frequent physical activity.…”
Section: Discussioncontrasting
confidence: 51%
“…A number of cross-sectional studies among adolescents found an association between physical inactivity and substance use: smoked more on a daily basis [2], smoking and other tobacco use, as well as alcohol consumption during the previous 30 days [3], alcohol consumption [4], cigarette smoking, marijuana use [5], initiation of cigarette smoking and alcohol use [6], cigarettes, smokeless tobacco, and marijuana [7].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of cross-sectional studies about relation between youth's free time activities and substance use have demonstrated a correlation between physical inactivity and drug usage; smoked more on a regular basis, 39 smoking and other tobacco use, as well as alcohol intake over the previous 30 days, 40 alcohol consumption, 41 cigarette smoking, marijuana consumption, 42 smoking and alcohol intake, 43 nicotine, smokeless tobacco, and marijuana intake. 44 In contrast, Matejovičová et al 21 failed to find a significant relation between leisure time sports activity and drug use among female university students in Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that time is spent on watching television or DVDs and on a computer rather than using these facilities. A study of trends in physical activity of Greenlandic schoolchildren showed that about one-quarter of the children were heavy television watchers, spending four hours a day or more [19].…”
Section: Discussionmentioning
confidence: 99%